Insurance Perspective in Eastern UP - An Empirical Study - Sharma, S. RaviKumar (Indian Journal of Marketing, 2005)
The task of the government is not to do the business but to regulate the business. Public enterprise in any country cannot perform all the economic and business activities efficiently and effectively. Even in a Socialist economy Public enterprise are not able to discharge all of their responsibilities. For last 57 years we have seen that the government has not been able to discharge the regulatory roles, promotional roles, entrepreneurial roles and planning roles. Baring a few enterprises in public sector (NTPC and Oil PSUs) all other sectors in public sector have not performed up to the mark. So government should appraise in this matter and return those fields back to the private sector, which have not performed well and needs participation. It has been the wrong public work culture environment, which has lead to the poor performance of the Public sector. In the year 1956, the basic objective of privatization of the insurance sector was governance and social welfare and security of people.